The use of response surface methodology to optimise malting conditions of quinoa (Chenopodium quinoa L.) as a raw material for gluten-free foods and beverages - Zankow, Martin; Geier, Thomas; Lindemann, Bernd; Burberg, Felix; Back, Werner; Arendt, Elke; Kreisz, Stefan (BrewingScience, 2007)
Response surface methodology was used to investigate the influence of the three malting parameters, degree of steeping, germination time and temperature, on the quality of quinoa malt. Each predictor variable was tested at three levels. Germination times were set to 5, 6, and 7 d, degrees of steeping were set to 46, 50, and 54 %, and germination temperatures were 8, 11.5, and 15 °C. A kilning temperature of 74 °C was used for all malts. A series of malt quality attributes was investigated including extract, β-amylase activity, limit dextrinase activity, α-amino nitrogen (FAN), and dimethyl sulfide precursor (DMSP). The optimal malting programme was achieved with 5 d germination time, 46 % degree of steeping, 15 °C steeping and germination temperature. The obtained amylolytic and proteolytic attributes were 59.6 % extract, 2021 U/kg limit dextrinase activity, 20 U/g β-amylase activity, 19.1 mg/100 mL FAN, and 12.7 mg/kg dimethyl sulfide precursor (DMSP). β-amylase activity could not be proved, therefore it was not considered for the evaluation.